2010
DOI: 10.3892/ijmm_00000454
|View full text |Cite
|
Sign up to set email alerts
|

Computational modeling of the potential interactions of the proteasome β5 subunit and catechol-Ο-methyltransferase-resistant EGCG analogs

Abstract: Abstract. (-)-Epigallocatechin gallate [(-)-EGCG] has beenimplicated in cancer chemoprevention and has been shown as an inhibitor of tumor proteasomal chymotrypsin-like activity in vitro and in vivo. However, EGCG is subjected to rapid biotransforming modifications such as methylation by catechol-O-methyltransferase (COMT) that limits its action. We recently reported that structure 7, an EGCG analog which should be resistant to COMT-mediated methylation and inactivation in cells, was able to inhibit the activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Recently, Moiseeva et al ( 2007 ) showed that low-dose long-term exposure of bioactive components such as EGCG and genistein results in epigenetic alterations of gene expression, reduced growth, and increased cellular apoptosis in breast cancer cells. Furthermore, there are several synthetic analogs of EGCG that have been shown to have strong anti-cancer activity with more efficacy and stability than EGCG under physiological conditions (Kanwar et al 2010 ; Huo et al 2010 ; Landis-Piwowar et al 2007 ). However, their epigenetic roles in cancer prevention and therapy have not yet been reported.…”
Section: Tea Polyphenolsmentioning
confidence: 99%
“…Recently, Moiseeva et al ( 2007 ) showed that low-dose long-term exposure of bioactive components such as EGCG and genistein results in epigenetic alterations of gene expression, reduced growth, and increased cellular apoptosis in breast cancer cells. Furthermore, there are several synthetic analogs of EGCG that have been shown to have strong anti-cancer activity with more efficacy and stability than EGCG under physiological conditions (Kanwar et al 2010 ; Huo et al 2010 ; Landis-Piwowar et al 2007 ). However, their epigenetic roles in cancer prevention and therapy have not yet been reported.…”
Section: Tea Polyphenolsmentioning
confidence: 99%